COMPARATIVE STUDY OF THREE EXTRACTION PROCESSES OF SECONDARY METABOLITES FROM LEAVES AND STEMS OF ARTEMISIA ANNUA (Asteraceae) - Rosine Désirée CHOUGOUO-NKUITCHOU KENGNE; Clemence N'Guessan Gnaman Clemence; Sylvain Landry Kouakou; Ernest Djoko; Awa Tuo Kouassi; Arthur Lia; Sandrine Aka Any-Grah; Alain N'Guessan; Ismaël Dally; Armand Koffi (Journal Africain de Technologie Pharmaceutique et Biopharmacie, 2023)
Introduction: Artemisia annua (Asteraceae) is a plant widely used to treat diseases including malaria. Manipulation conditions and treatment of plant influence physico-chemical characteristics and composition, so that objective of this work was to examine extraction processes in order to identify the best process that leads to obtain extracts with optimal pharmacotechnical characteristics and phytochemical properties for drugs formulation.